Review of 1971/03/20 Concert at St. Paul’s Church, Hockley. Concert of works by John Casken, Vaughan Williams and 15th Century English Composers given by students of Birmingham University under the direction of Nicholas Sandon and John Casken - Carver, Tony (Contact: A Journal for Contemporary Music (1971-1990), 1971)
-